Membangun Terobosan Baru di SD Negeri 091355 Urung Panei melalui Kontribusi Mahasiswa Program Kampus Mengajar 3 - Swasty Lumbanraja; Febrika Dwi Lestari; Sanggam Gultom; Wanri Lumbanraja; Kardi Manik; Nurliani Siregar (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
Kampus Mengajar Program aims to help equalize national education. This program is very much needed by schools with the background of Frontier, Remote and Disadvantaged (3T) or schools with C/B accreditation. Kampus Mengajar becomes a ledge for students and lecturers to participate in advancing national education. This program runs for 5 months or one semester. Kampus Mengajar Students Batch 3 performs 3 main tasks at the assignment, namely teaching, assisting with technology adaptation, and assisting school administration. SD Negeri 091355 Urung Panei is one of the target schools for the Kampus Mengajar. This school has a C accreditation and is in dire need of assistance, especially in improving students' literacy and numeracy skills. SD Negeri 091355 Urung Panei also needs additional teaching staff due to the shortage of teachers. Schools also need help to re-invigorate students' learning enthusiasm after 1.5 years of the COVID-19 pandemic.